Azolla microphylla Sebagai Biokonsentrasi Pencemaran Timbal (Pb) (Azolla microphylla As Bioconcentration of Lead (Pb) Pollution) - Guntur Althair Ahmady; Pindi Patana; Riri Ezraneti (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Lead (Pb) in water was found in dissolved and suspended form. Lead toxicity to plants was relatively lower compared to other trace elements. This study aimed to determine the influence of Azolla microphylla to absorb heavy metal at different concentrations of Pb, and Pb heavy metal for growth of Azolla microphylla biomass. This study was conducted from February to March 2014 in the Laboratory of Manajemen Sumberdaya Perairan Universitas Sumatera Utara.The ability of Azolla microphylla to absorb lead was measured by calculating Bioconcentration Factor. Results indicated that the BCF values on day H7 at 1 ppm of lead is 0.2372 and at 5 ppm is 0.3295. While on the H14 at 1 ppm concentration of lead is 0.2515 and at 5 ppm is 0.3536. Total weight of Azolla microphylla without lead contamination on day H7 is 105.6 grams, while the weight of Azolla microphylla with the addition 1 ppm of lead is 102.1 grams, and at 5 ppm is only 99.6 grams. While on the H14, the total weight of Azolla microphylla biomass without the addition of lead is 153.1 grams, 149.9 grams of lead at 1 ppm concentration, and 140.8 grams of lead at 5 ppm. Then in H28 measurements, weight Azolla microphylla biomass in the control treatment reached 209.7 grams, treatment with 1 ppm of lead reached 210.3 grams weight, and reached 198.5 grams at 5 ppm.Keywords : Azolla microphylla, Lead, BCF